Uso do micro-ondas como método de cozimento no protocolo de avaliação da maciez da carne bovina - Silva, Douglas Roberto Guimarães (2015)
The meat tenderness is an important parameter for the beef quality acceptance by consumers. There are various protocols used to determine the cooked meat tenderness, but the most used is the Warner-Bratzler Shear Force (WBSF) protocol, on which the grilling-based method is considered standard. Due to difficulties in standardizing this method, other alternatives have been studied, such as the microwave cooking method. In this study, we aimed to assess the use of microwave-based cooking method in the WBSF protocol for determining the beef tenderness, correlating its results with those from the standard protocol (grill cooking) and sensorial assessment. Steaks of striploin (M. Longissimus thoracis) beef with different tenderness degrees were cooked on a grill (Gr) and in the microwave oven, at 100% (Mw100) and 60% (Mw60) power, and assessed for shear force (SF) and sensory tenderness. The greater repeatability of SF was found for the Gr treatment (R=0.81), followed by the Mw100 (R=0.63) and then Mw60 (R=0.47). Was also found a strong correlation of SF with the sensory tenderness for Gr based method (r=0.86), followed by the Mw100 (r=0.68) and then Mw60 (r=0.65). Therefore, the grilling-based method was found to be suitable to assess the meat tenderness, but the use of microwave oven may also be an alternative, requiring to be studied some more, seeking to improve its standardization.